Between Order and Justice: Goethe's Stance on Violence - Rojas Alvarado, Arturo (2025)
The present article discusses Johann Wolfgang von Goethe’s (1749-1832) stance on violence, primarily based on his experience during the Siege of Mainz, through the notions of order and justice presented in some passages of his work.